EFFECT OF MIND–BODY EXERCISES VERSUS DIAPHRAGMATIC BREATHING EXERCISES ON BLOOD PRESSURE AND PERCEIVED STRESS IN YOUNG FEMALES - Ashna Waseem Patel; Heera Vijaykumar (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2025)
Introduction: Stress is a common psychosocial factor that adversely affects physical and mental health, particularly among young females who experience academic and interpersonal stressors. Chronic perceived stress can influence autonomic function and blood pressure (BP), increasing the risk of future lifestyle disorders. Mind–body exercises and diaphragmatic breathing exercises are known to reduce stress, but comparative evidence between these interventions is limited. This study aimed to compare their effects on BP and perceived stress in young females. Methodology: A comparative study was conducted on 30 young females aged 18–24 years with high perceived stress (PSS-10 score 27–40) and normal BP. Participants were selected using convenience sampling and randomly allocated into two groups: Group A (mind–body exercises) and Group B (diaphragmatic breathing exercises), with 15 participants each. Both groups received supervised intervention sessions of 15 minutes, three times per week for eight weeks. Blood pressure was measured at baseline, 4th week, and 8th week, while perceived stress was assessed using the PSS-10 at baseline and post-intervention. Statistical analysis was performed using appropriate parametric and non-parametric tests. Results: Both groups showed a statistically significant reduction in perceived stress levels after the intervention (p < 0.05). The effect size was moderate in Group A and moderate-to-large in Group B. No statistically significant changes were observed in systolic or diastolic BP within or between the groups. Comparison between the two interventions revealed no significant difference in post-intervention BP or perceived stress scores. Discussion: The findings suggest that both interventions are effective in reducing perceived stress among young females. The absence of significant BP changes may be attributed to normal baseline BP values and the relatively short intervention duration. Conclusion: Mind–body exercises and diaphragmatic breathing exercises are equally effective, simple, and safe methods for reducing perceived stress in young females and can be recommended as preventive stress management strategies.